Fe(III)-Chloroquine Complex: A New Potent Compound in Wellness Industries of High Antimicrobial and Antimalarial Activities - Thakur, Deepa; Mishra, Jyotsna; Pitre, K. S.; Joshi, Smita (International Journal of Biotechnology for Wellness Industries, 2013)
Fe(III)- Chloroquine complex has been synthesized and screened for its physicochemical, microbial as well as pharmacological activity have been done in solid and aqueous phase. On the basis of elemental analysis, polarographic studies, amperometric titration and IR spectral studies the probable formula for the complex has been determined at 25±1OC and ionic strength of µ= 1.0[KCl]. Raper’s paper disc method was used for microbial study against various pathogenic bacteria and fungi. In vivo syudy of Swiss mice [25-30gm] were used for antimalarial activity against Chloroquine and its complex on xyline-Alcoholic activity test Kidney, liver and serum of these rats were also studied. On the basis of observed result it could be concluded that Fe (III)-Chloroquine complex were found to be non-toxic and more potent than pure chloroquine drug.